Statistical study on Container Corporation of the Philippines - Gutano, Georgina D. (College of Engineerin, 2001)
Container Corporation of the Philippines is a manufacturing company that produces kraftlinerboards, boxboards, chipboards and corrugating mediums. Through the application of problem analysis tools, the corrugating medium was found to be the product line that has the most number of rejects. The major causes of rejection are high moisture content and low grammage. The speed was identified as a factor that influences moisture content and low grammage. The group utilized the one-way classification analysis of variance (ANOVA) of completely randomized design of experiment to determine if machine speed exhibits treatment effects on the aforementioned properties. The group found out that there is no relationship between moisture content and machine speed. Significant speed effect was only exhibited with basis weight, the response variable. Further statistical tests were conducted to determine the relationship between the machine speed and the basis weight. The scatter diagram and the linear regression equation revealed a negative relationship between the two variables. With the tests of means and variances, the group also found out that the only machine speeds of 300 and 310 meters per minute (mpm) produce CM 125 PQ with mean and standard deviation equal to the specifications of the company. The group recommends the use of machine speed of 310 mpm since it produces CM 125 PQ at a much faster rate and yet still produces corrugating medium that are within the company specification.